The effect of tungsten content on the properties of L12-hardened Co-Al-W alloys - Pyczak, Florian; Bauer, Alexander; Göken, Mathias; Lorenz, Uwe; Neumeier, Steffen; Oehring, Michael; Paul, Jonathan; Schell, Norbert; Schreyer, Andreas; Stark, Andreas; Symanzik, Felix (Journal of Alloys and Compounds, 2015)
Ternary Co-Al-W alloys with W contents between 8 and 11 at.% were investigated with respect to element partitioning, γ' solvus, γ' volume fraction, lattice mismatch and creep properties. W is enriched in the γ' precipitates and an increasing W content stabilizes this phase. The lattice mismatch is positive up to 900 °C and rafting occurs during creep with a preferred direction in accordance with this positive lattice mismatc
Keywords: Metals and alloys; Precipitation; Thermodynamic properties; Transmission electron microscopy TEM; X-ray diffraction